Effects of traditional Chinese exercises on the rehabilitation of patients with chronic heart failure: A meta-analysis - Dai, Mengqiao; Luo, Ziyan; Hu, Shuqin; Chen, Hu; Yang, Jiechao; Geng, Dandan; Li, Weina; Liao, Xiaoqin (Frontiers in Public Health, 2023)
Background: With the development of rehabilitation medicine, exercise therapy has gradually become one of the methods to prevent and treat cardiovascular diseases. It is widely used in clinic because it can further reduce the mortality rate, improve clinical symptoms, restore the activity ability of the body, improve the quality of life of patients and reduce the hospitalization rate. Traditional Chinese exercises have developed rapidly in recent years, which mainly include Baduanjin, Tai Ji etc. However meta-analyses of all types of exercises are not well characterized. Objectives: To evaluate the effect of traditional Chinese exercises (TCEs) on the rehabilitation of patients with chronic heart failure (CHF) using a meta-analysis. Methods: A systematic search of randomised controlled trials (RCTs) on TCEs for patients with CHF in 13 databases (PubMed,China National Knowledge Infrastructure,etc.).Meta-analysis was performed using Review Manager software (version 5.3) after two investigators independently screened the studies, assessed the quality of the studies, and extracted the data. Results: Meta-analysis of 21 randomised controlled trials which involved 1665 patients with chronic heart failure showed that practising TCEs was effective in improving patients' physiological outcomes such as VO2max [MD = 2.14, 95% CI (1.02, 3.26), P < 0.001], AT [MD = 1.61, 95% CI (1.06, 2.16), P < 0.001], and left ventricular ejection fraction (MD = 2.60, 95% CI [1.17, 4.02], P < 0.001). Non-physiological outcomes benefited from the application of TCEs: 6-minute walking distance [MD=38.55, 95% CI (36.67, 40.42), P<0.001], quality of life [MD =5.52, 95% CI (3.17,7.88), P < 0.001], and single-item TCM symptom scores in CHF patients: tiredness and fatigue [MD =0.78, 95% CI (0.03,1.53), P = 0.04], shortness of breath [MD=0.44,95% CI (0.26,0.62), P<0.0001], facial puffiness and limb swelling [MD=0.44,95% CI (0.12,0.76), P=0.007], palpitations [MD=0.68,95% CI (0.14,1.21), P=0.01] were improved. Conclusions: TCEs improved several recovery indicators, heart failure-related clinical symptoms, quality of life, and physiological indicators in patients with CHF. It is worthwhile to expand the participants for practical application in clinical practice, but the existing evidence is insufficient and the heterogeneity of outcome is large. Therefore, more high-quality clinical trials are needed to support these results.